Multi-objective optimization of planetary roller screw mechanism based on improved mathematical modelling. (September 2021) - Yao, Qin; Zhang, Mengchuang; Liu, Yongshou; Ma, Shangjun
Abstract: The optimization of obtaining the most uniform load distribution is important for the load carrying capacity design of the planetary roller screw mechanism (PRSM). However, the stiffness matrix of PRSM in traditional method based on the relationship between load and deformation of the thread may be destroyed when threads are no longer in contact due to machining errors, which would bring convergence problem in optimization process. In this paper, the mathematical model is firstly established to overcome the above drawbacks by proposing an improved iterative algorithm. Then, the multi-objective optimization is conducted to search the best designed pitches for the most uniform load distribution on both the screw-roller and nut-roller interfaces, and results are verified by the finite element method. Highlights: The mathematical model of load distribution considering pitch errors, pitch deviation and installation modes is established. An improved iterative algorithm is proposed to solve the divergent problems in previous methods. The effects of pitch errors and pitch deviation on the load distribution are is deeply studied. The multi-objective optimization is conducted to search the best designed pitches for the most uniform load distribution of PRSM.